Importance of genetics in conservation of biodiversity (2017)
Genetic diversity is the centre pillar for species and ecosystem diversities and the main goal of conservation genetics is to apply the knowledge of genetics to reduce the risk of extinction. Unfortunately, it has not received its deserved place in the biodiversity conservation efforts. This review is aimed at highlighting the need for the application of genetics in the conservation of natural resources and as well to assess the successes recorded so far while also identifying some challenges of conservation genetics. Non-invasive DNA sampling have been used to trace the origin of seized ivory tusk, detect hybridization, evaluate social structures in organisms, estimate population size and identify predator of kills. Poor adaptation of captive-bred endangered species when they are reintroduced to the wild, solving the problem of inbreeding and the high cost of conducting researches were identified as some of the challenges in the field of conservation genetics.